Wetlands Ecology Eco-biological uniqueness of a Ramsar site (East Kolkata Wetlands, India) - Chakraborty, Susanta Kumar; Sanyal, Poulomi; Ray, Ratnadeep (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book discusses current knowledge and challenges with the ecological management and conservation of wetlands, with a focus on the East Kolkata Wetlands of India. This area is referred to as a Ramsar Site, a designation given to areas with special protection statuses, since it is the largest natural waste recycling system in the world. The site faces many threats to its biodiversity and ecosystem functioning due to anthropogenic activity in the region, and therefore an assessment of the ecosystem services, bio-ecological uniqueness, and issues stemming from climate change and human impacts is needed to develop protection strategies for the future ecological functioning and sustainability of the wetlands. The authors use GIS and remote sensing techniques to assess and monitor harmful industrial and environmental impacts on the wetlands, and to inform mitigation and conservation strategies in the face of ongoing threats such as pollution, habitat destruction and bioinvasion. Thebook also highlights various social and economic aspects tied to the functioning and management of the wetlands, along with ecological, biological, and physio-chemical considerations. The study will be of use to students and researchers in aquatic ecology, biodiversity, and environmental sustainability and conservation, as well as to environmental planners, engineers, andpolicymakers. .
Chapter 1-Introduction -- Chapter 2-Historical perspectives of the wetlands with special reference to geomorphic evolution of East Kolkata Wetlands -- Chapter 3-Underlying ecological principles for the functioning of Wetland Ecosystems -- Chapter 4-Basics of Remote Sensing Techniques applicable in the aquatic freshwater system: Classificatory Approaches of East Kolkata Wetlands -- Chapter 5-Biodiversity of East Kolkata wetlands: Concept of biodiversity -- Chapter 6-Ecosystem services and values of Wetlands (East Kolkata Wetlands). Chapter 7-Seasonal Dynamics of Physico-Chemical Parameters of Soil and Water -- Chapter 8-Threats and pollution of wetlands: Special reference to East Kolkata Wetland (E.K.W) -- Chapter 9-Biomonitoring and Bioremediation -- Chapter 10-Sustainable conservation strategy (Waste Water Recycling) -- Chapter 11-Conclusion.
Keywords: Environmental management; Freshwater ecology; Marine ecology; Biotic communities; Environmental monitoring; Biodiversity; Environmental Management; Freshwater and Marine Ecology; Ecosystems; Environmental Monitoring; Biodiversity